1973
DOI: 10.1203/00006450-197307000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Environmental Temperature on Airway Resistance in the Asthmatic Child

Abstract: ExtractTo test the hypothesis that receptors to cold are in the upper air passages, the effect of a change in environmental temperature from a high of 90-95° F to a low of 50-55° F was studied in a group of eight children with a history of chronic asthma before and after applying topical anesthesia to nose and pharynx; nine children without cardiac or pulmonary disease served as control subjects. The forced expiratory volume in 1 sec (FEVi), the maximum voluntary ventilation (MVV), and the maximum expiratory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Consistent with these findings, there are reports indicating that cooling of the nasal cavity, and thus the inhalation of cold air through the nose, could induce bronchoconstriction [5,6,18]. In our study, however, tidal nasal breathing of subfreezing air without cooling the skin of the face had no effect on FEV1.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Consistent with these findings, there are reports indicating that cooling of the nasal cavity, and thus the inhalation of cold air through the nose, could induce bronchoconstriction [5,6,18]. In our study, however, tidal nasal breathing of subfreezing air without cooling the skin of the face had no effect on FEV1.…”
Section: Discussionsupporting
confidence: 79%
“…The set-up allowing nasal breathing of subfreezing air without cooling the rest of the body was thought to be of importance, since there is evidence to suggest the existence of cold or airflow-sensitive receptors in the nasal cavity [5,6,16,17]. Consistent with these findings, there are reports indicating that cooling of the nasal cavity, and thus the inhalation of cold air through the nose, could induce bronchoconstriction [5,6,18].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…ipratropium bromide were 38 1% (5-0), 34.5% (6-1), 11-3% (3)(4)(5)(6)(7), and 19-3% respectively. Similarly, the mean maximal falls in MMFR after saline, lignocaine, sodium cromoglycate, and ipratropium bromide were 54 4% (5-2), 52 9% (7 7), 23-6% , and 32-1% (10(5) respectively.…”
mentioning
confidence: 96%
“…Rodriguez-Martinez ct al. [9] showed that inhaled lignocaine could block bronchoconstriction due to inhalation of cool air, although they provide no information on the level of ventilation of their subjects at rest. In all the reported studies, only the maximum bronchoconstrictor effect of exercise or hyperventilation was used in the analysis of results as compared, in the present study, with a standardized index (PDim) derived from the dose response curve for which the between-day reproducibility has previously been assessed [13].…”
Section: Discussionmentioning
confidence: 99%